Heterothallism in Tilletia indica: Implications for physiological specialization - N.S. BAINS and R.C. SHARMA, I. SHARMA*, A. SIRARI, B. RAJ (Indian Phytopathology, 2008)
Monosporidiallines from three isolates, P 4 , P a , and P 2 of Karnal bunt fungus, T. indica were used to detect cross compatibility and mating alleles. Four mating alleles were identified in P4 isolate whereas 3 were identified when monosporidiallines of P 2 crossed with the lines of P a • Differential disease response was observed in a set of wheat varieties inoculated with 8 compatible monosporidial pairs which were categorized into highly, moderately and least aggressive groups. Further, the site of dikaryotization was indicated using monosporidia of opposite mating types as a tool. Inoculations with co-cultured compatible monosporidial pair for 15-20 days resulted in high level of disease in a susceptible variety, WH 542, indicating dikaryotization in vitro. Disease development with sequential inoculations of monosporidia of opposite mating types at intervals of 24 and 48 hrs revealed the possibility of dikaryotization within the host. Presence of mycelium in the young kernels from ear heads inoculated with the individual monosporidial lines, after 10 and 30 days, supported the possibility of dikaryotization within the host tissue.